Cognitive-Communication Performance Following Mild Traumatic Brain Injury: Influence of Sex, Age, Education, Site of Lesion and Bilingualism - LeBlanc, Joanne; Seresova, Alena; Laberge-Poirier, Andréanne; Tabet, Sabrina; Alturki, Abdulrahman Y; Feyz, Mitra; de Guise, Elaine (International journal of language & communication disorders, 2021)
Background: Although previous research studies have defined several prognostic factors that affect cognitive-communication performance in patients with all traumatic brain injury (TBI) severity, little is known about what variables are associated with cognitive-communication impairment in complicated mild TBI (mTBI) specifically. Aims: To determine which demographic and trauma-related factors are associated with cognitive-communication performance in the early recovery phase of acute care following a complicated mTBI. Methods & Procedures: Demographic and accident-related data as well as the scores on cognitive-communication skill measures in the areas of auditory comprehension (complex ideational material subtest of the Boston Diagnostic Aphasia Examination), verbal reasoning (verbal absurdities subtest of the Detroit Test of Learning Aptitude), confrontation naming (short form of the Boston Naming Test), verbal fluency (semantic category and letter category naming), and conversational discourse (conversational checklist of the Protocole Montréal d'évaluation de la communication) were retrospectively collected from the medical records of 128 patients with complicated mTBI admitted to a tertiary care trauma hospital. Multiple linear regressions analyses were carried out on the variables sex, age, education level, Glasgow Coma Scale (GCS) score, lesion site and bilingualism. Outcomes & Results: Females performed better than males on letter-category naming, while those more advanced in age performed worse on most cognitive-communication measures. Patients with higher education achieved better confrontation and letter-category naming, whereas reading comprehension results were worse with a lower GCS score. Bilingual individuals presented more difficulty in conversational discourse skills than those who spoke only one language. In terms of site of lesion, the presence of a right frontal injury was associated with worse auditory and reading comprehension and an occipital lesion was related to worse confrontation naming. Conclusions & Implications: Cognitive-communication skills should be evaluated early in all patients with complicated mTBI, but especially in those who are advanced in age, those with fewer years of education and those who present with lower GCS scores, in order to determine rehabilitation needs. The findings of this study will allow acute care clinicians to better understand how various demographic and injury-related factors affect cognitive-communication skills after complicated mTBI and to better nuance the interpretation of their evaluation results in order to improve clinical care. Further study is required regarding the influence of lesion location, sex and bilingualism following complicated mTBI.